Adoption of Waste Heat Recovery Technologies: Reviewing the Relevant Barriers and Recommendations on How to Overcome Them - Christodoulides, Paul; Aresti, Lazaros; Panayiotou, Gregoris P.; Tassou, Savvas A.; Florides, Georgios A. (My University, 2022)
The wide adoption of heat recovery technologies in industry is hampered by specific “barriers” related to both technical and non-technical issues. This paper attempts to determine these barriers and make recommendations on how to address them. First, a literature review of related material is presented. Among numerous barriers, the main ones identified are (i) lack of information, (ii) lack of technology knowledge, (iii) technology risks, (iv) high initial and running and maintenance costs, (v) lack of financial support and lack of governmental incentives, (vi) size and available space limitations, (vii) lack of available infrastructure, (viii) production constraints and risk of production disruptions, (x) risk of the system negative impact on the company operations, and (xi) policy and regulations restrictions. Then, based on the above, a structured questionnaire on barriers to the adoption of waste heat recovery (WHR) technologies was prepared and issued to a number of industries throughout the European Union. Upon analyzing the questionnaire, an assessment of the importance and negative impact of each of the above-mentioned barriers is made. Subsequently, strategies and recommendations on how to overcome the barriers is reported. These recommendations are hoped to be adopted as far as possible in the packaging, installation, commissioning, and demonstration of new and old WHR technologies.
Keywords: Waste heat recovery; WHR technologies; WHR Europe; EU industries; WHR barriers; WHR limitations